Recycling municipal solid waste incineration fly ash in super-lightweight aggregates by sintering with clay and using SiC as bloating agent. (November 2022) - Han, Siyu; Song, Yingchun; Ju, Tongyao; Meng, Yuan; Meng, Fanzhi; Song, Mengzhu; Lin, Li; Liu, Mengdan; Li, Jinglin; Jiang, Jianguo
Abstract: Municipal solid waste incineration (MSWI) fly ash is classified as hazardous waste and requires proper treatments. Sintering of MSWI fly ash for the production of lightweight aggregate (LWA) is a promising treatment technology, while the dependence on natural bloating clay to produce high quality LWA has limited its wide application. In this study, by using SiC as a bloating agent, normal clay could be used to produce super-lightweight aggregate (bulk density <500 kg/m 3 ) with MSWI fly ash. Effects of SiC addition amount, sintering temperature and duration on LWA performance were studied. The results showed that LWA with SiC addition of 0.1–0.5 wt% had significant expansion at sintering temperature of 1120 °C–1160 °C. The optimal conditions were 0.3 wt% SiC addition and sintering at 1120 °C for 30 min, and the bulk density could reach 212 kg/m 3 with other properties meeting the LWA standard (GB/T 17431.1-2010). Further, the heavy metal leaching toxicity was significantly decreased after sintering and met the MSWI fly ash utilization standard (HJ 1134–2020). The X-ray diffraction results revealed the formation of a complex diopside-based phase after sintering. This study provides a new approach for recycling MSWI fly ash in LWA without dependence on specific clay resources, and makes this technology wider applicability. Graphical abstract: Image 1 Highlights: SiC was applied as bloating agent to produce LWA with MSWI fly ash. Super-lightweight aggregate could be produced by adding 0.1–0.5 wt% SiC. Effects of SiC addition and sintering conditions were studied in detail. Risk of heavy metal leaching toxicity has been mitigated after sintering. Formation of complex diopside-based phase during sintering was revealed.